2014
DOI: 10.1007/s10008-014-2655-0
|View full text |Cite
|
Sign up to set email alerts
|

Mg2Al3, a complex and disordered intermetallic compound as anode material for metal-air batteries

Abstract: The intermetallic compound Mg 2 Al 3 has been selected for this work to be tested as anode in a metal-air battery. The compound is prepared by a high-temperature synthesis from elements and its cubic structure (Fd 3 m, a=28.2341(3) Å) has been refined from X-ray single crystal diffraction data. It is characterized by a high level of disorder with a large number of partially filled atomic sites, split positions, and atomic mixing. The compound displays an interesting behavior towards self-corrosion in alkaline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…139 Researchers have revealed that the intermetallic compound Mg 2 Al 3 displayed interesting behavior towards self-corrosion in alkaline and saline environments, but better electrochemical performances were obtained in NaCl electrolyte. 140 However, Mg, as a reactive metal, is also susceptible to corrosion in aqueous solutions, thus reducing the anodic utilization rate. 141 A series of studies proved that doping Mg with minor alloying elements (including Al, Li, Pb, Zn, Ce, Y, Bi, Sn, In, Ga, etc.)…”
Section: Development Of Nacl-based Electrolytes For Metal-air Batteriesmentioning
confidence: 99%
“…139 Researchers have revealed that the intermetallic compound Mg 2 Al 3 displayed interesting behavior towards self-corrosion in alkaline and saline environments, but better electrochemical performances were obtained in NaCl electrolyte. 140 However, Mg, as a reactive metal, is also susceptible to corrosion in aqueous solutions, thus reducing the anodic utilization rate. 141 A series of studies proved that doping Mg with minor alloying elements (including Al, Li, Pb, Zn, Ce, Y, Bi, Sn, In, Ga, etc.)…”
Section: Development Of Nacl-based Electrolytes For Metal-air Batteriesmentioning
confidence: 99%
“…Except for Mg2Al3, they are described with totally ordered atomic arrangements. The Bergman line would be extended to Mg4Zn7 (or Mg36Zn64) [33] and Mg2Al3 (or Mg37.3Al62.7, according to its true formula [34,35]). Similarly, Mg21Zn25 (or Mg45.7Zn54.3, e/a = 2) [36] and Mg17Al12 (or Mg58.6Al41.4, e/a = 2.41) [37] are located at both ends the Φ-phase domain.…”
Section: Structural Preferencesmentioning
confidence: 99%
“…[1][2][3] Recently, Mg alloys have also attracted attention as anodes in Mg-air batteries, which are considered to be a promising power source and energy storage device because of their high theoretical voltages, high current capacities, and environmental friendliness. [4][5][6][7] Mg-air batteries have a negative standard electrode potential (−2.37 V vs SHE), high Faradic capacity (2.2 Ah g −1 ), and relatively low density (1.74 g cm −3 ). 8 Among various types of metal-air batteries, Mg-air batteries have the highest theoretical cell voltage (3.1 V) and a higher specific energy density (6.8 kwh kg −1 ) than Zn-air batteries (1.3 kwh kg −1 ).…”
mentioning
confidence: 99%